Shuntug mga kabundukan sa kasaysayan at kalinangang Pilipino - Ubaldo, Lars Raymund C. (Adhika ng Pilipinas, Inc. National Commission for Culture and the Arts, 2015)
Traditional belief of Philippine ethnic groups towards mountains.